Migrasjonens materialitet - Ringdal, Siv (Tidsskrift for kulturforskning, 2016)
In the article a photo and two lumps of glass are the starting point for analyzing Norwegian-American migration history in the late 19th century. The author follows the three objects, and some other items which have belonged to the author’s family for generations, back in time and through their journey in space. In Norway the items were memorial objects of family history and a great-great-grandfather’s distant past in the US. The author shows how the photo and lumps of glass both reveals different aspects of this transatlantic history, but also suggests how the same objects have a biography, with several different meanings and functions through their journey in time and space. Immigrants’ experience with the urban American consumer society has not received much attention from Norwegian-American migration historians. In the article the author stresses how a closer look on materiality can be a fruitful methodological entrance to this part of Norwegian migration history. The author also stresses the importance of analyzing photos not merely as two dimensional motifs, but also as materiality.